Options for Mitigation in Agriculture - Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
Climate-Smart Agriculture Training for Practitioners: Asia Development Bank Presented 9-11 October 2018, Tokyo, Japan Session: Options for Mitigation in Agriculture